x + y = 82x - y = 5-------------------- add together to eliminate y3x = 13x = 13/3Substitute for x in one of the original equations:(13/3) + y = 8y = 24/3 - 13/3y = 11/3x=13/3 & y=11/3
Solving 11x-28=82x for x involves the following: -28=82x-11x -28=71x -28/71=x x=.3943 (truncated to 4 decimal places)
2x + 1 = 82x = 7x = 7/2 = 3.5whew !
x + 36 = 82x = 82 - 36x = 46
x = 59y = 23Let:x = the first numbery = the second numberx + y = 82 -- equation (1)x - y = 36 --- equation (2)By Elimination:x + y = 82x - y = 36=========2x = 118 2x/2 = 118/2x = 59x + y = 82y = 82 - xy = 82 - 59y = 23check:x - y = 3959 - 23 = 3636 = 36Let x = 1st numberlet y = 2nd numberX + Y = 82X - Y = 36add above equations2X = 118X = 59Y = 23
Y = 82x, the value of Y will be 82 times whatever value of x that is chosen
x + y = 82x - y = 5-------------------- add together to eliminate y3x = 13x = 13/3Substitute for x in one of the original equations:(13/3) + y = 8y = 24/3 - 13/3y = 11/3x=13/3 & y=11/3
Solving 11x-28=82x for x involves the following: -28=82x-11x -28=71x -28/71=x x=.3943 (truncated to 4 decimal places)
2x + 1 = 82x = 7x = 7/2 = 3.5whew !
x + 36 = 82x = 82 - 36x = 46
If that's -82x + 99, the answer is (3x - 11)(5x - 9) If that's +82x + 99, the answer is (3x + 11)(5x + 9)
x = 59y = 23Let:x = the first numbery = the second numberx + y = 82 -- equation (1)x - y = 36 --- equation (2)By Elimination:x + y = 82x - y = 36=========2x = 118 2x/2 = 118/2x = 59x + y = 82y = 82 - xy = 82 - 59y = 23check:x - y = 3959 - 23 = 3636 = 36Let x = 1st numberlet y = 2nd numberX + Y = 82X - Y = 36add above equations2X = 118X = 59Y = 23
Your answers are x = 1/2 (.5) & y = 1Given Equations:10x + 3y = 82x + y = 2Derived Equations:y = 2 - 2xSubstitution:10x + 3 * (2 - 2x) = 810x + 6 - 6x = 84x + 6 = 84x = 2x = 1/2 = .52 * (.5) + y = 21 + y = 2y = 1Check Answers:10 * (.5) + 3 * (1) = 82 * (.5) + (1) = 2
a = 3 and y = 0
y=9x=3it equals ......y= 3.334
x equals y
y=9